2021
DOI: 10.1111/jerd.12823
|View full text |Cite
|
Sign up to set email alerts
|

Enamel wear against monolithic zirconia restorations: A meta‐analysis and systematic review of in vitro studies

Abstract: Objective An assessment was performed to identify and evaluate dental enamel wear caused by monolithic zirconia restoration. Literature searches were conducted in PubMed, Science Direct, Cochrane Evidence, and the Cochrane Library up to May 2020. Material and methods Studies were selected for systematic review according to the inclusion (articles conducted on the wear of enamel samples opposing monolithic zirconia) and exclusion (case reports, non‐English articles, and monolithic zirconia samples facing other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 80 publications
1
14
0
1
Order By: Relevance
“…However, the zirconia tested by Habib et al was multi-layered, with a high amount of cubic phase, which is more prone to mechanical degradation and might lead to less uniform prism exposure and a consequent superficial roughness increase, which, therefore, explains the higher wear induced by this material compared with that obtained in the present study [24]. This was also confirmed by Sripetchdanond et al [13], who concluded that the materials inducing the least wear to enamel were RBC and zirconia, as well as different reviews that showed how zirconia has friendly wearbehaviour against enamel [14][15][16]. The present results were also confirmed by Ludovichetti et al [11], who reported a high abrasiveness of lithium disilicate, while nanofilled RBC and PINC were more antagonist-friendly.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, the zirconia tested by Habib et al was multi-layered, with a high amount of cubic phase, which is more prone to mechanical degradation and might lead to less uniform prism exposure and a consequent superficial roughness increase, which, therefore, explains the higher wear induced by this material compared with that obtained in the present study [24]. This was also confirmed by Sripetchdanond et al [13], who concluded that the materials inducing the least wear to enamel were RBC and zirconia, as well as different reviews that showed how zirconia has friendly wearbehaviour against enamel [14][15][16]. The present results were also confirmed by Ludovichetti et al [11], who reported a high abrasiveness of lithium disilicate, while nanofilled RBC and PINC were more antagonist-friendly.…”
Section: Discussionsupporting
confidence: 84%
“…Consistencies were reported by Habit et al [ 12 ], who found higher wear of the enamel when matched with zirconia. In contrast, different Authors [ 13 , 14 , 15 , 16 ] found different results, showing how zirconia produced less antagonist wear in comparison with PINC materials. These inconsistencies within apparently similar in vitro studies may be related to the different testing procedures adopted, as well as to the different polishing treatments of each material.…”
Section: Introductionmentioning
confidence: 91%
“…In laboratory studies, enamel wear by polished zirconia-based materials was less than or comparable to tooth–tooth contact; however, the wear behavior was dependent on the surface topography of the restorations [ 16 , 17 ]. In a previous systematic review [ 18 ], it was reported that there was no significant difference in the opposite enamel wear between zirconia-based materials and enamel in vitro. Moreover, in clinical studies, enamel wear by zirconia-based materials is larger than or comparable to tooth–tooth contact [ 9 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the wear property of crown-restorative materials is an important mechanical property for the long-term clinical success of tooth restoration. For dental CAD/CAM ceramics, numerous in vitro studies have been conducted to examine the wear behaviors of dental-restorative materials under simulated oral environments by comparing each material combination [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]: Ceramic vs. enamel antagonist, ceramic vs. ceramic antagonist, and enamel vs. enamel antagonist. Many studies have been conducted on the wear behavior of ZIR and LDS.…”
Section: Introductionmentioning
confidence: 99%